2015
DOI: 10.1111/fwb.12575
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and mapping the distribution, diversity and abundance of freshwater mussels (Family Unionidae) in wadeable streams of Illinois, U.S.A.

Abstract: 1. Freshwater mussels are one of the most imperilled animal groups in the world. Their effective conservation and restoration require a better understanding of their spatial distributions at a relevant scale and of their relationships with natural environmental factors and human disturbances. 2. In this study, we sampled over 900 sites on wadeable streams throughout Illinois, U.S.A., and compiled environmental data for a wide range of natural and anthropogenic factors related to climate, geology, land use, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 82 publications
1
30
0
Order By: Relevance
“…Cao et al. () found that the presence or absence of mussels was influenced by the per cent of urban land use in the total catchment area above the sampling location. Daniel and Brown () also showed that the amount of agricultural lands in the corridor were negatively associated with mussel density and richness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al. () found that the presence or absence of mussels was influenced by the per cent of urban land use in the total catchment area above the sampling location. Daniel and Brown () also showed that the amount of agricultural lands in the corridor were negatively associated with mussel density and richness.…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater mussels (Unionoida—hereafter “mussels”) can serve as a model system to study ecological baselines as reference conditions, in part because they are among the most threatened freshwater fauna in North America (Haag, ; Strayer et al., ). There are several suggested causes for these declines, including habitat loss and destruction (Williams, Warren, Cummings, Harris, & Neves, ), dams (Haag, ; Layzer, Gordon, & Anderson, ; Vaughn & Taylor, ), invasive species (Baker & Hornbach, ; Sousa, Novais, Costa, & Strayer, ) and land‐use change (Arbuckle & Downing, ; Atkinson, Julian, & Vaughn, ; Cao, Huang, & Cummings, ; Cao et al., ; Poole & Downing, ). However, few studies have determined specific causes of declines, and thus, long‐term impacts are often identified as responsible for decreases in population density and assemblage diversity (Downing, Van Meter, & Woolnough, ; Strayer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The modelling approach used here has rarely been used to model unionids in North America, where other modelling approaches have been favoured (but see Lois et al , for a similar approach in Europe). Typical methods for modelling mussel occurrences require localized, within‐stream habitat measurements integrated over a small stream segment (Allen & Vaughn, ; Atkinson et al , ; Campos et al , ; Gangloff & Feminella, ; Weber & Schwartz, ), which limits the spatial extent, or modelling the habitat suitability of entire catchments, which limits the resolution (Atkinson et al , ; Cao et al , ; Mynsberge et al , ; Weber & Schwartz, ). The method employed in this paper has a relatively high resolution and can encompass a very large spatial extent.…”
Section: Discussionmentioning
confidence: 99%
“…Such information can be difficult to obtain at regional spatial scales. Alternatively, mussel assemblages have been modelled at the catchment or sub-catchment scale, which limits the degree of resolution (Atkinson et al, 2012;Cao et al, 2015;Mynsberge, Strager, Strager, & Mazik, 2009). This approach fails to provide information identifying local habitat on the landscape, which has been shown to be necessary for effective conservation decisions.…”
Section: Correlations Between Species Richness and Precipitation In Wmentioning
confidence: 99%